MEDICINAL CLAY AS AN ADJUVANT IN SUPPORTIVE THERAPY IN CHRONIC PERIODONTITIS - Beresescu, Gabriela; Mucenic, Simona; Ormenisan, Alina; Monea, Adriana (European Scientific Journal, ESJ, 2014)
Medicinal clays can be used in the pharmaceutically products as an active ingredients, excipients or additives. The aim of this study is to assess the effects of the medicinal clay as an adjuvant in scaling and root planning in a non-surgical treatment of chronic periodontitis. Thirty subjects, aged between 25-60 were randomly distributed in two groups (test group and control group) according the inclusion and exclusion criteria. All the subjects received scaling and root planing. The test group received local instillation of the medicinal clay after scaling and root planing. The control group received no treatment with medicinal clay after scaling and root planing. The clinical parameters, porbing depth and clinical attachment level were assessed baseline (one day) and three months after the treatment protocol. The results showed significant improvement in clinical parameters. The results showed that in test group at baseline, the mean PD was 3.26 mm and CAL was 4.45, which decreased to 1.87 mm and 3.31 mm respectively (statistically significant p≤0.05). In conclusion, the effect of a medicinal clay used as an adjuvant in scaling and root planing has been proved.